IMPLIKASI HAK MENGUASAI NEGARA TERHADAP HAK MILIK PERORANGAN SEBAGAI POLITIK AGRARIA DALAM PENYELENGGARAAN ATAS TANAH - Merry Bogia, Amelia Febrina; Palguna, I Dewa Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013, 2013)
Land acquisition due to public necessity shall be grounded upon the basis of State Authoritative Rights, had implied towards derogation of personal ownership rights since the compensation granted due to the acquisition of land. It had triggered social disparity within society and increasing the level of poverty in Indonesia. Hence, this writing shall apply normative legal research and secondary data with statutory and conceptual approach. This writing shall also illustrate the basic provisions of State Authoritative Rights and personal ownership rights pursuant to the 1945 Constitution and Law No 5 of 1960 concerning Basic Regulations of Land Management and its acquisition procedure pursuant to the Law No 2 of 2012 concerning Land Acquisition Due to Public Necessity and President’s Decree No 71 of 2012 concerning On the Use of Land Acquisition Due to Public Necessity
Keywords: State Authoritative Rights, Individual Ownership Rights, Land Management